Seven Days of 100% Watermelon Juice Intake Improves Blood Pressure during Pregnancy: A Quasi-Controlled Intervention - Anggraeni, Lely; Ardiyani, Vissia Didin; Hatini, Erina Eka; Aden, Christine (Formosa Journal of Science and Technology, 2024)
This study assessed the impact of consuming watermelon juice at a concentration of 100% on blood pressure among pregnant women. For the duration of one week, thirty healthy pregnant women in good health participated in this quasi-experimental study by consuming 700 mL of 100% watermelon juice daily. Before and after each intervention, a blood sample was taken to ensure normal blood glucose. The evaluation of vascular function encompassed two assessments, including systolic and diastolic pressures. The study employed general linear models (GLM) to analyze the effects of the intervention, specifically focusing on intent-to-treat analyses. Although there was a notable treatment effect on the levels of blood pressure parameters (p < 0.000). The juice intervention yielded a modest yet statistically significant rise in decreasing blood pressure (p < 0.001), while there were no notable changes in other variables. The clinical significance of glucose balance was shown to be negligible. Prior research has provided evidence to substantiate the efficacy of watermelon extracts in enhancing vascular function among individuals. Therefore, we examined the benefit of it among pregnant women to prevent preeclampsia/eclampsia.